A Novel Technique for Managing Pancreaticojejunal Anastomotic Leak after Pancreaticoduodenectomy - Tufan Egeli; Tarkan Unek; Mucahit Ozbilgin; Mustafa Goztok; Ibrahim Astarcıoglu (Case Reports in Surgery)
Pancreaticoduodenectomy (Whipple’s procedure) remains the only definitive treatment option for tumors of the periampullary region. The most common and life-threatening complications following the procedure are pancreatic anastomotic leakage and subsequent fistula formation. When these complications occur, treatment strategy depends on the severity of anastomotic leakage, with patients with severe leakages requiring reoperation. The optimal surgical method used for reoperation is selected from among different options such as wide drainage, definitive demolition of the pancreaticojejunal anastomosis and performing a new one, or completion pancreatectomy. Here we present a novel, simple technique to manage severe pancreatic leakage via ligamentum teres hepatis patch.